PERTANGGUNGJAWABAN HUKUM AFFILIATOR YANG MEMPROMOSIKAN PRODUK MENYEBABKAN KERUGIAN KONSUMEN - Adli Fahmi Lubis, Muhammad; Sunarmi, Sunarmi; Siregar, Mahmul; Robert, Robert (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
Binomo as a trading platform has claimed many victims, this happened with the presence of affiliates who also promoted large amounts of profits obtained in a short time. Indra Kenz as an influencer and affiliate has been named a suspect. It is necessary to study the forms of misleading promotion that cause consumer losses, the mechanism for compensation for losses by affiliates to consumers and the legal responsibility of affiliates who promote products that cause consumer losses. This research is normative research using a statutory approach and a conceptual approach. Data uses secondary data sources, consisting of primary, secondary and tertiary legal materials collected using library study techniques. The data analysis used is qualitative analysis. The research found and concluded that forms of misleading promotions that cause consumer losses include misleading promotions with evidence of success and the promise of large profits promised by affiliates. The mechanism for returning losses to victims of Binary Options crimes is by filing a lawsuit for compensation, both civil and UUPK. Legal liability by affiliates who promote products that cause consumer losses can be subject to sanctions as stated in Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the ITE Law and Article 1365 of the Civil Code. If referring to Article 9 paragraph (1) letter k UUPK, then affiliates can be subject to sanctions in Article 62 paragraph (1) UUPK.